Early loading of 6‐mm‐short implants with a moderately rough surface supporting single crowns – a prospective 5‐year cohort study. Issue 4 (15th April 2014) - Rossi, Fabio; Lang, Niklaus P.; Ricci, Emanuele; Ferraioli, Lorenzo; Marchetti, Claudio; Botticelli, Daniele
Abstract Aim To evaluate prospectively the clinical and radiographic outcomes after 5 years of early loading of 6‐mm implants with a moderately rough (SLActive®) surface supporting single crowns in the posterior regions. Material and methods Thirty‐five consecutive patients received 40 SLActive® (Straumann) 6‐mm implants with a diameter of 4.1 mm (n = 19) or 4.8 mm (n = 21). Insertion torque and resonance frequency analysis (RFA) were measured at implant installation. RFA was also measured at abutment connection. SynOcta abutments were tightened with 35 Ncm after 6 weeks of healing, and single porcelain fuse to metal crowns was cemented within 1 week. Implant survival rate and marginal bone loss were evaluated at various time intervals until 5 years after loading. The clinical crown/implant ratio was calculated as well. Results Two of 40 implants were lost before loading (incorporation rate 95%), and no further implant loss or technical complications were encountered during the 5‐year follow‐up period. A mean marginal bone loss of 0.7 ± 0.6 mm was found after 5 years of function. The clinical crown/implant ratio increased with time from 1.6 at the delivery of the prosthesis to 2 after 5 years of loading. Conclusion Six millimeter implants with a SLActive® moderately rough surface supporting single crowns in the posterior region and loaded after 6–7 weeks maintained full function for at least 5 year with low marginal bone resorption.